Should Acellular Dermal Matrices Be Used for Implant-based Breast Reconstruction after Mastectomy? Clinical Recommendation Based on the GRADE Approach - Michela Cinquini, PhD; Nicola Rocco, MD, PhD; Giuseppe Catanuto, MD, PhD; Emanuele Garreffa, MD; Pietro Maria Ferrando, MD; Marien Gonzalez-Lorenzo, PhD; Anna Maglia, PhD; Giacomo Montagna, MD; Amedeo Villanucci, MD; Valentina Visintini Cividin, MD; Maurizio Bruno Nava, MD; GRADE MBN 2021 Collaborative Group; et al. (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Acellular dermal matrices (ADMs) entered the market in the early 2000s and their use has increased thereafter. Several retrospective cohort studies and single surgeon series reported benefits with the use of ADMs. However, robust evidence supporting these advantages is lacking. There is the need to define the role for ADMs in implant-based breast reconstruction (IBBR) after mastectomy. Methods:. A panel of world-renowned breast specialists was convened to evaluate evidence, express personal viewpoints, and establish recommendation for the use of ADMs for subpectoral one-/two-stage IBBR (compared with no ADM use) for adult women undergoing mastectomy for breast cancer treatment or risk reduction using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Results:. Based on the voting outcome, the following recommendation emerged as a consensus statement: the panel members suggest subpectoral one- or two-stage IBBR either with ADMs or without ADMs for adult women undergoing mastectomy for breast cancer treatment or risk reduction (with very low certainty of evidence). Conclusions:. The systematic review has revealed a very low certainty of evidence for most of the important outcomes in ADM-assisted IBBR and the absence of standard tools for evaluating clinical outcomes. Forty-five percent of panel members expressed a conditional recommendation either in favor of or against the use of ADMs in subpectoral one- or two-stages IBBR for adult women undergoing mastectomy for breast cancer treatment or risk reduction. Future subgroup analyses could help identify relevant clinical and pathological factors to select patients for whom one technique could be preferable to another.